Relationships between Lithospheric Flexure, Thrust Tectonics and Stratigraphic Sequences in Foreland Setting: the Southern Apennines Foreland Basin System, Italy - Critelli, Salvatore; Muto, Francesco; Tripodi, Vincenzo; Perri, Francesco (IntechOpen, 2011)
None